The Unintended Consequence of English Votes for English Laws. (August 2015) - Armstrong, Angus; Ebell, Monique
The Scotland Bill 2015–16 would make the Scottish government one of the most powerful sub-central governments in the OECD in terms of its control over spending and taxation. The UK government has also announced plans to introduce 'English Votes for English Laws' (EVEL), where the support of a majority of English MPs would be necessary to pass legislation deemed to impact on England only. The objective of this paper is to examine the potential for spillovers to arise in monetary unions of asymmetric nations where fiscal policy choices are taken locally. We extend a model ofChari and Kehoe (2008) to show the sub-optimal consequences of devolved fiscal policy in a moneteary union with a dominant member state. Because England is so much larger than the other constituent nations of the UK, its fiscal policy choices will have a commensurately stronger impact on UK monetary policy. As a result, UK monetary policy might be inappropriate for the smaller nations, calling into question the economic efficiency of EVEL. This is a general result which arises from the asymmetry of nations rather than specific UK funding arrangements or behavioural responses.